(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Apical or periapical lesions are inflammatory processes which are generally caused by microorganisms or their by-products and manifest due to defense response of the host to the stimulus in the root canal system. The aim of this study was to assess prevalence of periapical lesions among the south indian population. This was a descriptive study, where the data of the patients who reported to the dental clinics in saveetha dental college, SIMATS, Chennai, India, was obtained from the department of conservative dentistry and endodontics. Data was further analyzed, recorded in microsoft excel software and was subjected to statistical analysis. n = 15 for periapical lesions. From the data analysed through SPSS, it is observed that the prevalence of periapical lesions among non - vital teeth among the outpatients in the department of oral pathology is 1.1%. The age group of 60 - 70 years was the most commonly observed (60%). Male predilection was noted (67%). Radiographic examination was performed for 40% and histopathological examination was performed for 6.7% of the teeth with periapical lesions. 100% of the teeth observed in the current study were non - vital. Periapical abscess was the most common finding (53.3%). Occurring mostly in anterior maxillary, anterior mandibular and posterior mandibular regions (26.7%) each. The most commonly observed treatment modality was extraction (73.7%). Within the limitations of the current study , there exists increased prevalence of periapical pathology above 60 years, predominantly in the age group of 60 - 70 years, primarily reported in the undergraduate clinics. Routine dental checkup with both radiographic and histopathological examination of the periapical lesions is essential for the survival of the tooth and is beneficial for the community.